The impacts of road pricing on route and mode choice behaviour - Milenko Vrtic; Nadine Schuessler; Alexander Erath; Kay W. Axhausen (Journal of Choice Modelling, 2010)
This paper summarises the results of an extensive stated preference (SP) survey, conducted in Switzerland in order to obtain detailed information for the evaluation of road pricing schemes. Four different SP experiments were included: one about the political acceptability of road pricing and the other three about route, mode and departure time choice behaviour in the presence of road pricing. The questionnaires of 1005 respondents were used in a multinomial logit analysis of the latter three experiments. The values of travel time savings (VTTS) depended nonlinearly on the individual's income, travel time and overall travel costs. The respondents' evaluation of the cost components of fuel, tolls and parking differed significantly. Shifts in departure time depended on the choice situation were negatively valued. Furthermore, the importance of political preferences, as measured in the SP survey on acceptability, could be demonstrated, as the inclusion improved the model fit significantly as well as the reliability of the results.
Keywords: 330; GPS data; postprocessing; trip detection; activity detection; mode detection; fuzzy logic; map matching